2022
DOI: 10.3390/plants12010016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Physiological and Morphometric Characteristics and Biomass Distribution of Forage Grasses Growing under Conditions of Drought and Silicon Application

Abstract: Research on mitigating the effects of water scarcity by applying silicon to perennial grasses is still insufficient. This study was conducted to investigate the effect of spring and summer droughts and silicon applications on gas exchange parameters; the morphometric characteristics of root systems; and the biomass distribution of Festulolium braunii, Festuca arundinacea, and Lolium perenne cultivars. Plants were treated with a drought during the tillering phase once a year (during spring or summer regrowth) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
3
6
0
Order By: Relevance
“…4) and is consistent with the optimal allocation theory (McKey 1974). Similar results have con rmed the negative correlation between foliar Si and carbon concentrations (Klotzbücher et al 2018) and the reduced carbon content in Si applications (Mastalerczuk et al 2022). In addition, plants also adapt to minimize available light through the enhancement of light capture, for example, via the increased synthesis of chlorophyll and protein (Atanasova et al 2003).…”
Section: Discussionsupporting
confidence: 81%
“…4) and is consistent with the optimal allocation theory (McKey 1974). Similar results have con rmed the negative correlation between foliar Si and carbon concentrations (Klotzbücher et al 2018) and the reduced carbon content in Si applications (Mastalerczuk et al 2022). In addition, plants also adapt to minimize available light through the enhancement of light capture, for example, via the increased synthesis of chlorophyll and protein (Atanasova et al 2003).…”
Section: Discussionsupporting
confidence: 81%
“…The same was also observed when the seeds of the examined species were germinated as a mixture. Our other pot studies [ 40 ] have shown that while drought conditions reduced the root lengths of L. perenne in the tillering phase by approx. 40–50% compared to control conditions, the application of Si significantly increased the length of the roots (approx.…”
Section: Discussionmentioning
confidence: 88%
“…The diminution in flag leaf biomass, water content, succulence degree, succulence, succulence quotient, area, and specific area can be ascribed to several drought-induced phenomena: (i) a decline in cellular turgor pressure, ostensibly obstructing cell division, enlargement, and differentiation [ 59 ], (ii) an encumbered assimilate supply, largely attributed to the limitations imposed on critical plant processes, predominantly photosynthesis [ 60 ], (iii) a perturbation in nutrient availability, concomitant with a diminished water supply [ 61 ], and/or, (iv) a temporal shift, manifesting as delayed leaf emergence and precipitated leaf senescence [ 62 ].…”
Section: Discussionmentioning
confidence: 99%